Joint Flexibility and Myalgic Encephalomyelitis/Chronic Fatigue Syndrome After Mononucleosis - Poomkudy, Jeffrey Thomas; Torres, Chelsea; Jason, Leonard A.; Fishbein, Joseph; Katz, Ben Z. (Clinical therapeutics, 2024)
•At least 10% of patients meet criteria for ME/CFS 6 months following IM.•Previous reports associated joint hypermobility and ME/CFS.•In a prospective study we found no relation between joint mobility and ME/CFS. Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a chronic disease characterized by substantial fatigue, postexertional malaise, unrefreshing sleep, and orthostatic intolerance, among other symptoms. Specific risk factors for the development of ME/CFS have not been adequately characterized. It has been suggested that ME/CFS is a connective tissue disorder and that joint hyperflexibility is a risk factor for the development of ME/CFS. The goal of this study was to examine whether joint hyperflexibility is a risk factor for the development of ME/CFS after infectious mononucleosis (IM). This study was part of a prospective cohort study. College students were studied for the development of IM and were followed up for the development of ME/CFS 6 months later. Participants in the cohort for the present study included 53 students who met criteria for ME/CFS 6 months after IM and 66 recovered control subjects who had modified Beighton scores (a measure of joint hyperflexibility) available. No connection was found between joint hyperflexibility and the development of ME/CFS after IM. Differences in joint hyperflexibility (as measured by using the modified Beighton score) in the ME/CFS group and the control group were not statistically significant. Female subjects had significantly higher Beighton scores compared with male subjects. After IM, no relationship was found between joint hyperflexibility and the development of ME/CFS.